2000
DOI: 10.1097/00006982-200003000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Patients With Visual Field Defects Following ~ Macular Hole Surgery Using Multifocal Electroretinography

Abstract: Vitrectomy including removal of the ILM leads to expedited resolution of diffuse diabetic macular edema and improvement of visual acuity without subsequent epiretinal membrane formation. Complete release of tractional forces and inhibition of reproliferation of fibrous astrocytes seem to be prudent in the eyes of patients with diabetes and advanced vitreoretinal interface disease of the macula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 0 publications
2
67
1
1
Order By: Relevance
“…Our results do not support Gandorfer et al [3] that ILM removal led to an earlier and greater decrease of retinal thickness or to an earlier and better visual acuity. However, we agree with them that the tangential traction by a single layer of fibrous astrocytes on the vitreal surface of the ILM can cause macular edema.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results do not support Gandorfer et al [3] that ILM removal led to an earlier and greater decrease of retinal thickness or to an earlier and better visual acuity. However, we agree with them that the tangential traction by a single layer of fibrous astrocytes on the vitreal surface of the ILM can cause macular edema.…”
Section: Discussioncontrasting
confidence: 99%
“…Gandorfer et al [3] have supplemented the pars plana vitrectomy with internal limiting membrane (ILM) peeling, and reported an earlier and more significant reduction of macular edema in diabetic patients, and an improvement of visual acuity. They attributed the better results to the removal of all elements that could exert traction on the retina by the ILM removal.…”
Section: Introductionmentioning
confidence: 99%
“…7,106,201,216,251,283,295 Patients with macular hole were found to have marked reductions in mfERG response densities in both the foveal and perifoveal regions. 283,295 After successful macular hole surgery, improvement in foveal and perifoveal mfERG response densities could be observed.…”
Section: Central Serous Chorioretinopathymentioning
confidence: 99%
“…106,216 Oh et al found that none of the patients with visual field defects after macular hole surgery had specific abnormalities on mfERG and the findings suggested arteriolar occlusion is not a likely cause for the visual field defects. 216 Horio et al also used mfERG to evaluate the functional outcome in patients who underwent internal limiting membrane (ILM) peeling in macular hole surgery with or without indocyanine green (ICG) dye staining. 106 It was shown that there were no significant differences in P1 implicit time and amplitude ratios between the two groups.…”
Section: Central Serous Chorioretinopathymentioning
confidence: 99%
See 1 more Smart Citation